About Preserving Your Own Soul: Based on the Emancipantes of Bolesław Prus - Głąb, Anna (Roczniki Filozoficzne, 2024)
In this text, the author attempts to interpret Boleslaw Prus’ novel Emancipantes, referring to the story of the main character, Madzia Brzeska, and Professor Debicki’s metaphysical lecture. She believes that there is a connection between the metaphysical theses and the ethics of the novel’s heroine. According to her, Prus tries to present a unique philosophy of life in the novel, which is based on the achievements of the natural sciences of the time, but also on the inclusion of a religious component. The most important thing in the novel, however, is to give man a place in this philosophy of life and to assign him a moral task. First, she briefly (I) presents the historical context of the creation of Prus’ novel, then (II) moves on to the existential plot, i.e. Madzia’s adventures, and then (III) she concentrates on to Dębicki-Prus’ confession de foi, in which he acknowledges the existence of an immortal soul and eternal life. Finally, (IV) she reflects on the permanence of the metaphysics contained in Debicki’s lecture.